Повышение точности измерения магнитного датчика непосредственного контроля перемещения вагонов маятниковых подвесных канатных дорог - Чунашвили, Бадур Михайлович; Кобалия, М. И. (НТУ "ХПИ", 2010)
Creation of sensor with high preciseness and reliability for movement of hanging carriages acceptable for conditions of complex mechanical part of the electric drive of PHR with intermediate bearer is an urgent issue as it constitutes guarantee for realization of optimum dynamic tachogram. The work proposes method and based on it there is elaborated improved version of the magnetic drive of the immediate control of movement of carriages of PHR for application of electric drives of PHR with intermediate bearer.
Improvement of preciseness of the magnetic sensor metering of the immediate control of the movement of carriages of the pendulous hanging ropeways
Keywords: тахограмма; электропривод; импульс